Infant feeding practices in the first six months of life among HIV positive mothers attending Teaching Hospitals in Lagos, Nigeria - Olatona FA; Ginigeme ON; Roberts AA; Amu EO (Nigerian Journal of Paediatrics, 2024)
Background: In the absence of any interventions, 5-20% of infants born to HIVinfected women will be infected through breastfeeding.